Deregulation of PAX2 expression in renal cell tumours: mechanisms and potential use in differential diagnosis. Issue 8 (26th July 2013) - Patrício, Patrícia; Ramalho‐Carvalho, João; Costa‐Pinheiro, Pedro; Almeida, Mafalda; Barros‐Silva, João Diogo; Vieira, Joana; Dias, Paula Cristina; Lobo, Francisco; Oliveira, Jorge; Teixeira, Manuel R.; Henrique, Rui; Jeronimo, Carmen
Abstract Expression of PAX2 (Paired‐box 2) is suppressed through promoter methylation at the later stages of embryonic development, but eventually reactivated during carcinogenesis. Pax‐2 is commonly expressed in the most prevalent renal cell tumour (RCT) subtypes—clear cell RCC (ccRCC), papillary RCC (pRCC) and oncocytoma—but not in chromophobe RCC (chrRCC), which frequently displays chromosome 10 loss (to which PAX2 is mapped). Herein, we assessed the epigenetic and/or genetic alterations affecting PAX2 expression in RCTs and evaluated its potential as biomarker. We tested 120 RCTs (30 of each main subtype) and four normal kidney tissues. Pax‐2 expression was assessed by immunohistochemistry and PAX2 mRNA expression levels were determined by quantitative RT‐PCR. PAX2 promoter methylation status was assessed by methylation‐specific PCR and bisulfite sequencing. Chromosome 10 and PAX2 copy number alterations were determined by FISH. Pax‐2 immunoexpression was significantly lower in chrRCC compared to other RCT subtypes. Using a 10% immunoexpression cut‐off, Pax‐2 immunoreactivity discriminated chrRCC from oncocytoma with 67% sensitivity and 90% specificity. PAX2 mRNA expression was significantly lower in chrRCC, compared to ccRCC, pRCC and oncocytoma, and transcript levels correlated with immunoexpression. Whereas no promoter methylation was found in RCTs or normal kidney, 69% of chrRCC displayed chromosome 10 monosomy, correlating with Pax‐2 immunoexpression. We concluded that Pax‐2 expression might be used as an ancillary tool to discriminate chrRCC from oncocytomas with overlapping morphological features. The biological rationale lies on the causal relation between Pax‐2 expression and chromosome 10 monosomy, but not PAX2 promoter methylation, in chrRCC.